Matching-adjusted indirect comparison between garadacimab and lanadelumab for the long-term prophylactic treatment of patients with hereditary angioedema - Sarah Walsh; Anja Haltner; Meaghan Bartlett; John Sears; Yinglei Li; Maebh Kelly; Simona Gavata-Steiger; Chiara Nenci; Iris Jacobs; Ingo Pragst; Neelanjana Ray; Imtiaz A Samjoo (Journal of Comparative Effectiveness Research)
Aim: This study aimed to estimate the relative efficacy between garadacimab 200 mg once monthly (200 QM) and two dosing regimens of lanadelumab (300 mg once every 2 weeks [300 Q2W] and 300 mg once every 4 weeks [300 Q4W]) in adolescent/adult patients with hereditary angioedema (HAE) using matching-adjusted indirect comparisons (MAICs), in the absence of head-to-head randomized controlled trials. Materials & methods: Individual patient data were available from the phase II (NCT03712228) and the phase III VANGUARD (NCT04656418) trials investigating garadacimab, and published summarylevel data from the phase III HELP trial investigating lanadelumab (NCT02586805). The primary outcome was time-normalized number of HAE attacks. Secondary efficacy outcomes included time-normalized number of HAE attacks requiring on-demand treatment, time-normalized number of moderate and/or severe HAE attacks, and proportion of attack-free patients. Quality of life (QoL) was also assessed via change from baseline in AE-QoL total score. Results: Compared with lanadelumab 300 Q2W, garadacimab 200 QM statistically significantly reduced number of moderate and/or severe HAE attacks (rate ratio [RR]; 95% confidence interval: 0.25; 0.07, 0.84) and improved AE-QoL score (mean difference: -17.38; - 33.67, -1.08). Compared with lanadelumab 300 Q4W, garadacimab 200 QM showed statistically significant improvements in all outcomes: HAE attacks (RR: 0.29; 0.13, 0.63), attacks requiring on-demand treatment (RR: 0.29; 0.13, 0.66), moderate and/or severe HAE attacks (RR: 0.15; 0.05, 0.49), proportion of attackfree patients (hazard ratio: 3.25; 1.45, 7.29), and AE-QoL score (mean difference: -21.29; -37.39, - 5.18). Conclusion: These MAICs showed improved efficacy and QoL with garadacimab compared with lanadelumab across multiple endpoints. These findings demonstrate that garadacimab may provide improved therapeutic benefit compared with lanadelumab in the long-term prophylactic treatment of patients with HAE.